The intellectual foundations of modern Ukraine - Zayarnyuk, Andriy, 1975- author.
1 online resource.
Keywords: "This is the first synthetic book-length study in English of the Ukrainian nation-building during the "long" nineteenth century. The Intellectual Foundations of Modern Ukraine is the ideal resource for upper-level undergraduates, postgraduates, and scholars interested in cultural anthropology, political science, political philosophy, and the history of modern Ukraine"--